Development and optimization of Philippine raspberry jam using response surface methodology - Madamba, Isabella Maria H.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Response surface methodology was used to optimize formulations of Philippine raspberry jam. Nineteen formulations with varying levels of citric acid (0-0.75%), pectin (0-2%) and sugar (43-53%) were processed using a balanced incomplete block design. Response variables, measured with consumers (n=38) participating in the test, were overall acceptability as well as acceptance of appearance using a 9-point hedonic scale and viscosity, spreadability, sweetness and sourness using a 9-point category scale. Regression analysis was performed and models were built for each significant (p<0.05) response variable. Contour plots for each attribute, were generated and superimposed to determine the areas of overlap. Of the six responses measured, only appearance, spreadability, sourness and overall acceptability were significant. The optimum formulation obtained for Philippine raspberry jam was 49% sugar, 0.65% citric acid, and 0.30% pectin. Predicted and observed values from verification studies were not significantly different from one another; therefore, the models were valid. Some values were significant, however; this may be due to changes in the raw material used.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Jam; Raspberry